The Mexican entrepreneur - Derossi, Flavia (Paris : Development Centre of the Organisation for Economic Cooperation and Development, 1971)
This book examines entrepreneurship in Mexico with particular reference to industrialization.
Includes bibliographical references: p. 409-428.
lje 17/01/2018
Loans
Keywords: Businesspeople; Entrepreneurship; Industrial policy; Investments, Foreign